The dictionary of lost words : a novel - Williams, Pip, 1969- (Ballantine Books, 2020)
"The Dictionary of Lost Words is a work of fiction. All incidents and dialogue, and all characters with the exception of some well-known historical figures, are products of the author's imagination and are not to be construed as real. Before the lost word, there was another. It arrived at the Scriptorium in a second-hand envelope, the old address crossed out and Dr Murray, Sunnyside, Oxford, written in its place. It was Da's job to open the post and mine to sit on his lap, like a queen on her throne, and help him ease each word out of its folded cradle. He'd tell me what pile to put it on and sometimes he'd pause, cover my hand with his, and guide my finger up and down and around the letters, sounding them into my ear. He'd say the word, and I would echo it, then he'd tell me what it meant"--